PERFORMANCE EVALUATION OF SOME LOCALLY FABRICATED COOKSTOVES IN MUBI, ADAMAWA STATE, NIGERIA (Nigerian Journal of Technology, 2015)
In this study, four solid fuel household cook-stoves in Mubi, Adamawa state were tested for performance using the water Boiling Test (WBT) protocol. Results from the study showed that metal charcoal stove had the highest efficiency of 20.02%, followed by clay charcoal stove with 17.06%, then Metal shield stove with 11.64% and the lowest is the 3-stone fire with 9.46%. The metal charcoal stove had the lowest specific fuel consumption with the consumption value of 0.075, then clay charcoal stove with 0.100, followed by Metal Shield stove with 0.175 and the 3 – stone stove with the value of 0.225. The metal shield stove had the fastest time to boil 2kg of water at 12 minutes 30 seconds, while clay charcoal stove had the least time of 21 minutes 51 seconds to boil the same quantity of water. Values obtained for burn rates and fire power were 0.0285kg/min, 0.028kg/min, 0.008kg/min, 0.009kg, and 0.525W, 0.516W, 0.225W, 0.253W for 3 – stone stove, metal shield, metal charcoal and clay charcoal stoves respectively. In general, results from the testing showed that some stoves currently used in Mubi have improved fuel efficiency and higher thermal efficiency compared with the traditional cooking method. Better solid fuel cookstoves implies reduced fuel use, reduced deforestation and reduced air pollution.  http://dx.doi.org/10.4314/njt.v35i1.8